Heart failure across the range of preserved ejection fraction in United States clinical practice. (3rd October 2022) - Greene, S; Spertus, J A; Tang, W; Kang, A; Zhong, Y; Myers, M; Shen, S; Jiang, J; Liu, X; Steffen, D R; Viola, M; Felker, G M
Abstract: Introduction: Recent clinical trials of heart failure with preserved ejection fraction (HFpEF) have observed varying patient profiles by ejection fraction (EF), with attenuation of treatment benefits as EF increases. In routine clinical practice, the degree to which patients hospitalized for HF with EF≥60% may differ from those with lower EF is unknown. Purpose: To compare patient characteristics, treatment patterns, and clinical outcomes across the range of EF among patients hospitalized for HFpEF. Methods: Using the Humedica electronic medical records database between Jan 2010 and Dec 2020, patients hospitalized for a primary diagnosis of HF with EF>40% and who were haemodynamically stable at admission, without concurrent acute coronary syndrome or end-stage renal disease, and treated with intravenous (IV) diuretic agents within 48 h of admission were identified. Patient characteristics, treatment patterns, and clinical outcomes were compared by EF ranges of 41–49%, 50–59%, and ≥60%. Results: Of 47, 026 patients hospitalized with HFpEF, 6, 335 (13%) had EF 41–49%, 18, 603 (40%) had EF 50–59%, and 22, 088 (47%) had EF≥60%. Across all 3 groups, patients were similar with respect to age (median 77 years for each group), race (83–84% White, 12–13% Black), systolic blood pressure (137–138 mmHg at admission), and eGFR (63–64 mL/min/1.73 m 2 at admission). With progressively higher EF group, the proportion of women increased (45% vs 54% vs 65%) and median NT-proBNP decreased (4, 221 vs 2, 945 vs 2, 234 pg/mL). Patients with EF ≥60% had the lowest rates of coronary artery disease and atrial fibrillation, and the highest rates of chronic pulmonary disease (Figure 1, Panel A). Discharge medications were generally similar, with exception of less beta-blocker use and more calcium channel blocker use among those with EF ≥60% (Figure 1, Panel B). Discharge use of angiotensin receptor-neprilysin inhibitor and sodium glucose cotransporter-2 inhibitor therapies were each <1% in all groups. Hospital length of stay (median 4 days for each group) and in-hospital mortality (1.1–1.3%) were similar across groups, but rates of in-hospital acute respiratory failure were higher among patients with EF ≥60% (27% vs 230-25% for lower EF groups). Rates of 30-day and 12-month post-discharge clinical events were high irrespective of EF, without meaningful differences between groups (Figure 2). Conclusion: In a contemporary real-world population of US patients hospitalized for HF with EF >40%, nearly half had an EF≥60%. While clinical profiles and discharge medications varied, post-discharge outcomes were similarly poor irrespective of EF. There remain important opportunities to improve the care and outcomes for patients with HF across the range of preserved ejection fraction. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): MyoKardia, Inc., a wholly owned subsidiary of Bristol Myers Squibb